EARLY MARRIAGE OF MADURESE WOMEN IN THE AUTHOR’S WOMEN’S FICTION (NARATOFEMINIMS STUDY) - Oktasari, Anisa Fajriana; Suyatno; Ahmadi, Anas (Proceedings of International Conference on Islamic Civilization and Humanities, 2024)
Several Madurese-born female authors have mentioned many stories about early marriages and arranged marriages among Madurese women. This story was raised because this exists in the Madurese social community. To reduce this, the education that needs to be instilled in the Madurese generation is the instilling of the value of progress in the world of education, so that it continues to spread to the Madurese interior community. After investigation, this problem arises from various factors including economics, culture, religion and education. The narrative style of Madurese authors’ fiction will be highlighted in this article. This research uses a literary phenomenology approach with descriptive qualitative methods, analysis techniques combining fictional stories and the author’s statements in the field. The results of this research will find the causes of early marriage, arranged marriages among Madurese women, and the consequences that will arise, using the scalpel of naratofeminism theory. The fiction featured in this article is by a female Madurese writer who has received many awards from Joe Mawar, Muna Masyari, and Elok Teja Suminar.